Clinical relevance of different papillary growth patterns of pulmonary adenocarcinoma - Warth, Arne; Muley, Thomas; Harms, Alexander; Hoffmann, Hans; Dienemann, Hendrik; Schirmacher, Peter; Weichert, Wilko (The American journal of surgical pathology, 2016)
Growth patterns of pulmonary adenocarcinoma (ADC) have high prognostic impact and are accepted as a novel classification system for this entity. However, specifically for the papillary pattern, divergent data with respect to prevalence, clinical associations, and prognostic impact have been reported
Gesehen am 10.06.2020